(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2020)
This paper aims to analyse the representation of the Church as an ideological system that can be found in the end of the only novel written by the Equadorian writer Juan Montalvo - Capítulos que se le olvidaron a Cervantes - considering that this part of the book summarizes, in a brief and synthetic way, the main orientations of his social beliefs about the constitution of the Catholic church and its members. The analysis will be based on a contextualization of the origin of the novel and on Montalvo’s main ideological premises, according to some of his essays. Likewise, I will comment the effects that these ideological foundations carried to the conformation of the central characters of the novel. The study is based on the concept of Ideological Systems of the State conceived by Althusser (2013) and the idea of Ideology and Social Representations designed by van Djik (1991).